The Cognitive Turn
XVI, 260 p.
Keywords: If nothing else, the twelve papers assembled in this volume should lay to rest the idea that the interesting debates about the nature of science are still being conducted by "internalists" vs. "externalists,"" rationalists" vs. "arationalists, n or even "normative epistemologists" vs. "empirical sociologists of knowledge. " Although these distinctions continue to haunt much of the theoretical discussion in philosophy and sociology of science, our authors have managed to elude their strictures by finally getting beyond the post-positivist preoccupation of defending a certain division of labor among the science studies disciplines. But this is hardly to claim that our historians, philosophers, sociologists, and psychologists have brought about an "end of ideology," or even an "era of good feelings," to their debates. Rather, they have drawn new lines of battle which center more squarely than ever on practical matters of evaluating and selecting methods for studying science. To get a vivid sense of the new terrain that was staked out at the Yearbook conference, let us start by meditating on a picture. The front cover of a recent collection of sociological studies edited by one of us (Woolgar 1988) bears a stylized picture of a series of lined up open books presented in a typical perspective fashion. The global shape comes close to a trapezium, and is composed of smaller trapeziums gradually decreasing in size and piled upon each other so as to suggest a line receding in depth. The perspective is stylized too.